Biomaterial-supported Tissue Reconstruction or Regeneration - Barbeck, Mike; Jung, Ole; Smeets, Ralf; Koržinskas, Tadas (IntechOpen, 2019)
This book is a collection of chapters from different biomaterial experts, including their design, new insights into the molecular basis of their interaction with the organism, and their successful application. The chapters have been organized to illustrate different aspects of multidisciplinary biomaterial science. Thus, this book should give readers a view into the different biomaterial disciplines and methodologies that are needed for specific clinical applications.